Exploring copy number variants in deceased fetuses and neonates with abnormal vertebral patterns and cervical ribs. Issue 18 (4th August 2020) - Schut, Pauline C.; Brosens, Erwin; Van Dooren, Tom J. M.; Galis, Frietson; ten Broek, Clara M. A.; Baijens, Inge M. M.; Dremmen, Marjolein H. G.; Tibboel, Dick; Schol, Martin P.; de Klein, Annelies; Eggink, Alex J.; Cohen‐Overbeek, Titia E.
Abstract: Background: Cervical patterning abnormalities are rare in the general population, but one variant, cervical ribs, is particularly common in deceased fetuses and neonates. The discrepancy between the incidence in the general population and early mortality is likely due to indirect selection against cervical ribs. The cause for the co‐occurrence of cervical ribs and adverse outcome remains unidentified. Copy number variations resulting in gain or loss of specific genes involved in development and patterning could play a causative role. Methods: Radiographs of 374 deceased fetuses and infants, including terminations of pregnancies, stillbirths and neonatal deaths, were assessed. Copy number profiles of 265 patients were determined using single nucleotide polymorphism array. Results: 274/374 patients (73.3%) had an abnormal vertebral pattern, which was associated with congenital abnormalities. Cervical ribs were present in 188/374 (50.3%) and were more common in stillbirths (69/128 [53.9%]) and terminations of pregnancies (101/188 [53.7%]), compared to live births (18/58, 31.0%). Large (likely) deleterious copy number variants and aneuploidies were prevalent in these patients. None of the rare copy number variants were recurrent or overlapped with candidate genes for vertebral patterning. Conclusions: The large variety of copy number variants in deceased fetuses and neonates with similar abnormalities of the vertebral pattern probably reflects the etiological heterogeneity of vertebral patterning abnormalities. This genetic heterogeneity corresponds with the hypothesis that cervical ribs can be regarded as a sign of disruption of critical, highly interactive stages of embryogenesis. The vertebral pattern can probably provide valuable information regarding fetal and neonatal outcome.